Development and maintenance of the brain's immune toolkit: Microglia and non‐parenchymal brain macrophages. Issue 6 (24th October 2017) - Lopez‐Atalaya, Jose P.; Askew, Katharine E.; Sierra, Amanda; Gomez‐Nicola, Diego
ABSTRACT: Microglia and non‐parenchymal macrophages located in the perivascular space, the meninges and the choroid plexus are independent immune populations that play vital roles in brain development, homeostasis, and tissue healing. Resident macrophages account for a significant proportion of cells in the brain and their density remains stable throughout the lifespan thanks to constant turnover. Microglia develop from yolk sac progenitors, later evolving through intermediate progenitors in a fine‐tuned process in which intrinsic factors and external stimuli combine to progressively sculpt their cell type‐specific transcriptional profiles. Recent evidence demonstrates that non‐parenchymal macrophages are also generated during early embryonic development. In recent years, the development of powerful fate mapping approaches combined with novel genomic and transcriptomic methodologies have greatly expanded our understanding of how brain macrophages develop and acquire specialized functions, and how cell population dynamics are regulated. Here, we review the transcription factors, epigenetic remodeling, and signaling pathways orchestrating the embryonic development of microglia and non‐parenchymal macrophages. Next, we describe the dynamics of the macrophage populations of the brain and discuss the role of progenitor cells, to gain a better understanding of their functions in the healthy and diseased brain. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 78: 561–579, 2018